The Role of Youth Groups in Community Peace Building: Case of Amani Kibra and Kibera Hamlets in Kibra Informal Settlements, Kenya - Onguka, Janet Awuor; Wachira, Teresia Wamuyu; Wando, Antony Odek (International Journal of Conflict Management, 2024)
Purpose: The purpose of this study was to explore the role of youth groups in community peacebuilding, focusing on the Amani Kibera and Kibera Hamlets groups within Kibra's informal settlements in Kenya. Methodology: Anchored on Paul Lederach’s Conflict Transformation Framework, the study employed a mixed-methods approach, involving 40 respondents from Kibera Hamlets and 35 from Amani Kibera, selected through purposive and cluster sampling. Data collection included in-depth interviews, focus group discussions (FGDs), and structured questionnaires. Qualitative data were thematically analyzed, while quantitative data were processed using SPSS Version 28. Findings: Findings indicate that youth groups primarily focus on "Mentoring and Empowerment" (27.8%) and "Arts and Creative Expression" (26.9%), but encounter challenges such as resource limitations and socio-political instability, leading to ineffective support from religious institutions, government agencies, and NGOs. The study concludes that youth groups are essential for addressing community challenges and recommends expanding arts initiatives, improving resources, and using online platforms to enhance peacebuilding in Kibera. Unique Contribution to Theory, Policy and Practice: This study uniquely contributes to theory, policy, and practice in informal settlements by offering actionable, context-specific recommendations grounded in empirical evidence. It provides valuable insights into how innovative collaboration fosters trust and social capital, serving as an important resource for policymakers.